Item and scale properties of the Oral Health Literacy Adults Questionnaire assessed by item response theory. (10th December 2020) - Pattanaik, Swaha; John, Mike T.; Kohli, Nidhi; Davison, Mark L.; Chung, Seungwon; Self, Karl; Naik, Amruta; Flynn, Priscilla M.
Abstract: Objectives: a) To evaluate the item and scale properties of the Oral Health Literacy Adults Questionnaire (OHL‐AQ) in an adult general population. b) To determine precision or accuracy of the respondents' estimated scores along the Oral Health Literacy (OHL) spectrum using item response theory (IRT) modeling. Methods: Survey data were collected from a convenience sample of 405 adult attendees of the 2014 Minnesota State Fair. We used the two‐parameter logistic (2PL) model for the item response theory (IRT) analyses of OHL‐AQ data and calibrated items to estimate model‐based item difficulty and discrimination parameters. Item and scale properties were also assessed by plotting and interpreting item characteristic curves (ICCs), test characteristic curve (TCC), and test information function (TIF). Results: Based on interpretation of model coefficients, statistical testing, and model fit criteria, we deemed the 2PL model superior and selected this model to examine item and scale properties. Scale reliability was shown to be good through the test information function (TIF). TIF from our analysis showed that higher levels of OHL were measured less precisely than lower levels of OHL. Conclusion: We demonstrated OHL‐AQ as a whole has promising psychometric properties. However, for equiprecise measurement across the scale range, the scale needs more items for measuring higher levels of OHL.